Upaya Guru Mata Pelajaran IPS Terpadu Dalam Menanamkan Karakter Disiplin dan Tanggung Jawab Siswa - Sarika, Suci; Haloho, Bongguk; Napitu, Ulung (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The background of this research originates from the discovery of a lack of discipline and responsibility of students in the classroom.This study aims to identify and analyze the efforts of social studies teachers in instilling the character of discipline and responsibility of students through integrated social studies learning in class. This study used qualitative research methods. Through this research, it is hoped that the efforts of Integrated IPS subject teachers in instilling the character of discipline and responsibility, namely through the principles of Contextual Teaching and Learning (CTL) in which the teacher links the material he is learning with real-world situations of students. Some of the obstacles in cultivating the character of discipline and responsibility include a) family factors, b) environmental factors, c) internal factors in students. While the solution to the obstacles in instilling the character of discipline and responsibility is through, a) Control from the school principal, b) The active role of the teacher, c) control from parents.